A combinatorial approach for studying the effect of Mg concentration on precipitation in an Al–Cu–Li alloy. (1st January 2016) - Gumbmann, E.; De Geuser, F.; Deschamps, A.; Lefebvre, W.; Robaut, F.; Sigli, C.
Graphical abstract: Abstract: We apply a combinatorial approach to study the influence of Mg concentration on the precipitation kinetics in an Al–Cu–Li alloy using a diffusion couple made by linear friction welding. The precipitation kinetics is monitored in the composition gradient material using simultaneous space and time-resolved in-situ small-angle X-ray scattering measurements during ageing, and the strengthening of the precipitates is evaluated by micro-hardness profiles. This data provides an evaluation of the amount of Mg necessary to promote precipitation of the T1 –Al2 CuLi phase.